2003
DOI: 10.1007/s00248-002-2027-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Production in Relation to Microphytobenthic Biofilm Development: An Integrated Approach in a Tidal Mesocosm

Abstract: Experiments were performed to evaluate short-term changes in sediment extracellular carbohydrates for a multispecific assemblage of benthic diatoms in relation to physiological status, endogenous migratory rhythms, and environmental conditions. For this purpose, a mesocosm was used, which simulated both tidal and dark: light alternating cycles under controlled conditions. Scanning electronic microscopy in combination with picture analyses indicated that natural diatom migration patterns were reproduced in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 37 publications
8
63
1
1
Order By: Relevance
“…In these environments, they consist of epipelic raphid species endowed with endogenous migratory rhythms, which control their vertical movements across the sediment (Underwood & Kronkamp 1999). Extensive mats are produced during emersion periods where copious amounts of extracellular polymeric substances (EPS) are produced in relation to motility and/or nutrient limitation (Orvain et al 2003). MPB is rarely affected by nutrient limitation (Jesus et al 2009) because muddy sediments are enriched in organic matter and the decomposition by bacteria in deep layers stimulates a very active mineralization of nutrients that constitute an essential part of MPB nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In these environments, they consist of epipelic raphid species endowed with endogenous migratory rhythms, which control their vertical movements across the sediment (Underwood & Kronkamp 1999). Extensive mats are produced during emersion periods where copious amounts of extracellular polymeric substances (EPS) are produced in relation to motility and/or nutrient limitation (Orvain et al 2003). MPB is rarely affected by nutrient limitation (Jesus et al 2009) because muddy sediments are enriched in organic matter and the decomposition by bacteria in deep layers stimulates a very active mineralization of nutrients that constitute an essential part of MPB nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of colloidal material during immersion accounted for almost 80-90% of the colloidal and EPS carbohydrate produced during the previous illuminated emersion phase; with ϳ50% of this washed away and the remainder either lost through dissolution or bacterial activity. These high turnover rates will result in only a slow net accumulation of material over time (Orvain et al 2003). …”
Section: Discussionmentioning
confidence: 99%
“…EPS components may be removed into the overlying water column during high tide (either by physical erosion of surface sediment or by dissolution) (Underwood and Smith 1998b;Orvain et al 2003), used directly by deposit-feeding invertebrates and vertebrates (Decho 2000) or microbial heterotrophs (Decho 2000;Middelburg et al 2000;Hamels et al 2004), or degraded by photolysis (Moran et al 2000). The relative importance of each of these processes is likely to vary depending on the properties of individual EPS types.…”
mentioning
confidence: 99%
“…In our study, however, no biofilm was present (unlike in the above-mentioned studies) to be able to focus on the effect caused solely by C. volutator. Thus, in our experiment, complexity was reduced by excluding confounding factors such as the presence of a biofilm, since it is proven more than once that the presence of a biofilm increases water content of the surface sediment (Defew et Orvain et al 2003). The presence of a biofilm might explain why in some studies no difference was found between a control with biofilm and treatments with Corophium.…”
Section: Physical Impact Of Corophium Volutatormentioning
confidence: 98%